The Role of Islamic Religious Education Teachers in Moral Development of Students at SMP Negeri 1 Indra Jaya - Nazaruddin (MANDAILING GLOBAL EDUKASIA, 2024)
This study investigates the role of Islamic Religious Education (IRE) teachers in the moral development of students at SMP Negeri 1 Indra Jaya, a public junior high school in Aceh, Indonesia. Amidst the growing concerns over youth moral decline, the presence of IRE teachers is seen as a critical element in fostering students’ ethical awareness and behavior through the integration of religious teachings within the formal education system. Utilizing a qualitative research method with a case study approach, data were gathered through interviews with IRE teachers, school principals, and students, alongside classroom observations and document analysis. The findings highlight that IRE teachers play multifaceted roles—as educators, moral exemplars, counselors, and facilitators of religious practice. Their contribution goes beyond the cognitive delivery of religious knowledge; they actively engage in shaping students' character by instilling core Islamic values such as honesty, empathy, responsibility, discipline, and respect. The study also underscores the importance of teacher-student interaction, school culture, and extracurricular religious activities in supporting moral development. Through consistent modeling of good behavior and integration of moral lessons into everyday learning, IRE teachers contribute significantly to building students' moral foundations. The research concludes that effective moral education requires a holistic strategy that combines religious instruction, personal example, and a supportive school environment. These findings have important implications for educational policy and teacher training programs, especially in multicultural and secular school settings where moral education is often fragmented. Further research is suggested to explore the comparative roles of IRE teachers in urban and rural contexts to enrich the understanding of moral development across diverse educational landscapes.